2019
DOI: 10.3390/jcm8122113
|View full text |Cite
|
Sign up to set email alerts
|

The Right Time to Safely Re-Evaluate Empirical Antimicrobial Treatment of Hip or Knee Prosthetic Joint Infections

Abstract: Currently, no guideline provides recommendations on the duration of empirical antimicrobial treatment (EAT) in prosthetic joint infection (PJI). The aim of our study was to describe the time to growth of bacteria involved in PJI, rendering possible decreased duration of EAT. Based on a French multicentre prospective cohort study, culture data from patients with confirmed hip or knee PJI were analysed. For each patient, five samples were processed. Time to positivity was defined as the first positive medium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…As mentioned above, the Gram-positive bacteria growing after day 5 were C. acnes, followed by CoNS and Streptococcus spp. Similar findings were reported previously, e.g., in a French study aiming at estimating the right time to reevaluate EAT in hip and knee prosthetic joint infections, where more than 96% of the OAI-causing organisms were identified by day 5 and where the bacteria identified after 5 days were only Gram-positive bacteria, with only one case of Enterobacterales (20). Therefore, we propose adapting EAT by continuing daptomycin as monotherapy in order to reduce patient exposure to broad-spectrum antibiotics as well as to their individual and collective side effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As mentioned above, the Gram-positive bacteria growing after day 5 were C. acnes, followed by CoNS and Streptococcus spp. Similar findings were reported previously, e.g., in a French study aiming at estimating the right time to reevaluate EAT in hip and knee prosthetic joint infections, where more than 96% of the OAI-causing organisms were identified by day 5 and where the bacteria identified after 5 days were only Gram-positive bacteria, with only one case of Enterobacterales (20). Therefore, we propose adapting EAT by continuing daptomycin as monotherapy in order to reduce patient exposure to broad-spectrum antibiotics as well as to their individual and collective side effects.…”
Section: Discussionsupporting
confidence: 89%
“…Polymicrobial OAI, which represent 42% of OAI in our setting, were documented later than monomicrobial OAI. However, as in other studies, only Gram-positive bacteria grew after 5 days (20)(21)(22) in both mono-and polymicrobial OAI. Only three GNB grew after the first 2 days, but still within 5 days after sampling.…”
Section: Discussionsupporting
confidence: 80%
“…In terms of resistance patterns, most of the microorganisms involved in the SSIs in this study were susceptible to conventional antibiotics for bone and joint infections [40]. For the remaining microorganisms, we found that only 2.8% were MRSE and 3.2% were multidrug-resistant MRSE, for which conventional per os therapeutic options can be used such as cotrimoxazole, linezolid, and fusidic acid.…”
Section: Resistance Pattern Analysismentioning
confidence: 65%
“…In our practice, an aggressive DAIR is performed at the slightest suspicion of infection, with replacement of the mobile implants whenever possible. We associate an intravenous probabilistic antibiotic treatment, using the association piperacillin-tazobactam + linezolid [40,45], after performing bacteriological sampling secondarily tailored to the microorganisms detected intraoperatively (Supplementary Table S1). This probabilistic approach aims to provide early infection treatment so as to limit delayed or chronic infections of any material implanted for reconstruction [46].…”
Section: Resistance Pattern Analysismentioning
confidence: 99%
“…The two final studies of this issue are related to the treatment of PJI. Firstly, Deroche et al examined the optimal time for the safe re-evaluation of the empirical antibiotic choice during the operative treatment of hip and knee PJI [14]. The authors analysed data from 183 confirmed PJIs and concluded that almost 97% of all positive cultures were available within five days after the surgery when the culture protocol was optimised.…”
mentioning
confidence: 99%